2008
DOI: 10.1093/ecam/nen034
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years Evidence‐Based High‐Tech Acupuncture Part 3: A Short Review of Animal Experiments

Abstract: High-tech acupuncture research has been performed for 10 years at the Research Unit of Biomedical Engineering in Anesthesia and Intensive Care Medicine at the Medical University of Graz. This article as a part of a series comprises animal experiments in the field of needle and laser acupuncture. The investigations presented in this article were performed in pigs, dogs and sheep. In all studies sedative stimulation effects of the acupoint Yintang are described using different measurement parameters (EEG-bispect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Pressurization was achieved using a power disconnected regular autoclave (Selecta, Presoclave 30, J.P. Selecta SA) modified to work as a hyperbaric chamber by means of a connection of a pressurized oxygen cylinder to the draining tube of the autoclave. Animal breathing inside the chamber was stimulated with a previous injection of doxapram chlorhydrate and needle insertion at the acupuncture GV26 point (Litscher 2010). As there were no previous references for reptiles, the most commonly used human recompression-decompression table was applied (Vann et al 2011).…”
Section: Treatmentmentioning
confidence: 99%
“…Pressurization was achieved using a power disconnected regular autoclave (Selecta, Presoclave 30, J.P. Selecta SA) modified to work as a hyperbaric chamber by means of a connection of a pressurized oxygen cylinder to the draining tube of the autoclave. Animal breathing inside the chamber was stimulated with a previous injection of doxapram chlorhydrate and needle insertion at the acupuncture GV26 point (Litscher 2010). As there were no previous references for reptiles, the most commonly used human recompression-decompression table was applied (Vann et al 2011).…”
Section: Treatmentmentioning
confidence: 99%
“…In this process, biomedical engineers have become actively involved in the design, development and utilization of devices and new techniques [1] . The Research Unit of Biomedical Engineering in Anesthesia and Intensive Care Medicine at the Medical University of Graz (http://litscher.info) has been dealing with the development and implementation of new instruments, especially in the field of high-tech acupuncture research for more than 14 years [2][3][4][5][6][7][8][9][10][11][12] . Acupuncture has been used for medical treatment for thousands of years.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of empirical data is available but the technical quantification of effects was ORIGINAL ARTICLE not possible until now. Using electro-acupuncture, needle or laser needle stimulation and modern biomedical techniques, it was possible to quantify changes in biological activities caused by acupuncture [2][3][4][5][6][7][8][9][10][11][12] . In the middle of the 20th century, researchers found lower skin resistance of acupuncture points compared to non acupuncture sites.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, LA is expected to work by suppressing the pain under neurological and humoral mechanisms, such as the when using the needles [1,33]. Researches comparing acupuncture with needles and LA have shown equality in treatment efficiency between the two methods [4,5,10,34]. Some authors showed that the irradiation of acupuncture points with the low power laser induces different stimulations of the cerebral cortex [3,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Researches comparing acupuncture with needles and LA have shown equality in treatment efficiency between the two methods [4,5,10,34]. Some authors showed that the irradiation of acupuncture points with the low power laser induces different stimulations of the cerebral cortex [3,[34][35][36]. The partly placebo-controlled, randomized cross-over animal experimental pilot studies showed that needling and laser stimulation of the acupoint Yintang and other points can induce effects on parameters of bioelectrical brain activity (bispectral index, SEF 95), whereas the stimulation of control points did not yield significant changes [3,34].…”
Section: Discussionmentioning
confidence: 99%